Investigations on the Antifungal Effect of Nerol against Aspergillus flavus Causing Food Spoilage - Jun Tian; Xiaobin Zeng; Hong Zeng; Zhaozhong Feng; Xiangmin Miao; Xue Peng (The Scientific World Journal)
The antifungal efficacy of nerol (NEL) has been proved against Aspergillus flavus by using in vitro and in vivo tests. The mycelial growth of A. flavus was completely inhibited at concentrations of 0.8 μL/mL and 0.1 μL/mL NEL in the air at contact and vapor conditions, respectively. The NEL also had an evident inhibitory effect on spore germination in A. flavus along with NEL concentration as well as time-dependent kinetic inhibition. The NEL presented noticeable inhibition on dry mycelium weight and synthesis of aflatoxin B1 (AFB1) by A. flavus, totally restraining AFB1 production at 0.6 μL/mL. In real food system, the efficacy of the NEL on resistance to decay development in cherry tomatoes was investigated in vivo by exposing inoculated and control fruit groups to NEL vapor at different concentration. NEL vapors at 0.1 μL/mL air concentration significantly reduced artificially contaminated A. flavus and a broad spectrum of fungal microbiota. Results obtained from presented study showed that the NEL had a great antifungal activity and could be considered as a benefit and safe tool to control food spoilage.